Jihad dan Terorisme Dalam Perspektif Hukum Islam - Hidayatussalam Hidayatussalam; Muh. Mufti M. Djafar (Jurnal Budi Pekerti Agama Islam, 2024)
Jihad and Terrorism in the Perspective of Islamic Law (Hidayatussalam and Muhammad Mufti M. Djafar). Jihad and terrorism are two terms that have recently become the focus of international attention. The international community assumes that these two terms are manifested as movements of several activist groups that In Islam there are two sides that cannot be separated. Islamic history has noted that jihad and terrorism are not new phenomena, but each has a different history. Jihad emerged when Islam came, brought by the Prophet SAW, and became popular when the Prophet SAW moved to Medina. Meanwhile, terrorists emerged since the political constellation among the Shi'a which was spearheaded by Hasan bin Sabah, known as a splinter group of the Assassin sect, a splinter of the Shi'a Islᾱmiyyah group which allowed the murder of political opponents from the Bani Seljuq whom they claimed had gone astray in the 11th century and 13th. Jihad and terrorism are two terms that have recently become the focus of international attention. The international community assumes that these two terms, which have become the movements of several activist groups in Islam, are two sides that cannot be separated.